Sequential organ failure assessment score improves survival prediction for left ventricular assist device recipients in intensive care. Issue 9 (17th April 2022) - Chatterjee, Subhasis; Jentzer, Jacob C.; Kashyap, Rahul; Keegan, Mark T.; Dunlay, Shannon M.; Passe, Melissa A.; Loftsgard, Theodore; Murphree, Dennis H.; Stulak, John M.
Abstract: Background: Preoperative risk scores facilitate patient selection, but postoperative risk scores may offer valuable information for predicting outcomes. We hypothesized that the postoperative Sequential Organ Failure Assessment (SOFA) score would predict mortality after left ventricular assist device (LVAD) implantation. Methods: We retrospectively reviewed data from 294 continuous‐flow LVAD implantations performed at Mayo Clinic Rochester during 2007 to 2015. We calculated the EuroSCORE, HeartMate‐II Risk Score, and RV Failure Risk Score from preoperative data and the APACHE III and Post Cardiac Surgery (POCAS) risk scores from postoperative data. Daily, maximum, and mean SOFA scores were calculated for the first 5 postoperative days. The area under receiver‐operator characteristic curves (AUC) was calculated to compare the scoring systems' ability to predict 30‐day, 90‐day, and 1‐year mortality. Results: For the entire cohort, mortality was 5% at 30 days, 10% at 90 days, and 19% at 1 year. The Day 1 SOFA score had better discrimination for 30‐day mortality (AUC 0.77) than the preoperative risk scores or the APACHE III and POCAS postoperative scores. The maximum SOFA score had the best discrimination for 30‐day mortality (AUC 0.86), and the mean SOFA score had the best discrimination for 90‐day mortality (AUC 0.82) and 1‐year mortality (AUC 0.76). Conclusions: We observed that postoperative mean and maximum SOFA scores in LVAD recipients predict short‐term and intermediate‐term mortality better than preoperative risk scores do. However, because preoperative and postoperative risk scores each contribute unique information, they are best used in concert to predict outcomes after LVAD implantation. Abstract : In a retrospective review of 294 CF‐LVAD recipients, SOFA scores accurately predicted postoperative outcomes to one year.